Journal publication success of German business researchers: Does gender composition and internationality of the author team matter? - Martin Eisend; Pakize Schuchert-Güler (Business Research, 2015)
The authors analyze whether publication success of journal articles by authors from German-speaking countries is related to gender composition and internationality of the author team. The database for the analysis covers 7,464 articles that were published in peer-reviewed journals between 2008 and 2012 and that were (co-)authored by business researchers from German-speaking countries. The articles were ranked according to the quality of the journal an article was published in, using three prominent journal rankings in business research. The findings indicate that journal publication success is significantly higher in predominantly male and predominantly international author teams, and this relationship is even stronger the more selective the ranking is. The findings also indicate an interaction between gender composition and internationality. The findings vary across disciplines in business research depending on the average share of female coauthors in a discipline. Since the substantial differences in publication success for author teams that vary in gender composition are rather small and we even find a tendency of female authors to be more productive than male authors, these findings show that providing equal opportunities for female and male researchers that is a goal in its own right does not hurt science but can benefit research outcomes.
Keywords: 650; Journal publication success; Gender composition; Internationality; Business research